Pain and Delirium in Critical Illness: An Exploration of Key 2018 SCCM PADIS Guideline Evidence Gaps - Pisani, Margaret A.; Devlin, John W.; Skrobik, Yoanna (Seminars in Respiratory and Critical Care Medicine, 2019)
Managing pain and delirium are crucial to patients, families, and caregivers in intensive care units. The Society of Critical Care Medicine 2018 Pain, Agitation/Sedation, Delirium, Immobility, and Sleep disruption (PADIS) guidelines reviewed literature until October 2015 and made its recommendations for critically-ill adults. This chapter addresses evidence gaps, identified during the guideline process, most relevant to clinicians, adds newer evidence published after the PADIS 2018 guidelines were produced, describes hindsight-driven PADIS process or content-related gaps, and reflects on how these considerations may help inform future research investigations and new guideline efforts.
Keywords: pain; delirium; intensive care; critical care; practice guidelines; knowledge translation